Analisis Keaktifan Belajar Siswa Terhadap Model Pembelajaran Problem Based Learning (PBL) Pada Mata Pelajaran IPA Di Kelas V SD Kanisius Hasanudin Semarang - Astuti, Desy Eka Widy; KHB, Moh. Aniq; Budiman, M. Arief (Universitas Nusantara PGRI Kediri, 2019)
The background that drives this research is the fifth grade students of SD Kanisius Hasanudin Semarang who have very good learning activeness. Class V students are so enthusiastic when learning takes place. This can be seen from the response of students when the teacher gives small questions and students will scramble to raise their hands to answer questions from the teacher. Then the researcher wants to know whether the application of the Problem Based Learning model of learning students is more active in learning science. In addition, researchers also want to know what are the factors that influence the learning activities of fifth grade students of SD Kanisius Hasanudin Semarang. This type of research is descriptive qualitative. Data collection in this study was carried out by the method: interview, observation, questionnaire and documentation. The results of the study based on interviews with the teacher said that students were more active with the application of the Problem Based Learning learning model.